Mastering leadership an integrated framework for breakthrough performance and extraordinary business results - Anderson, Robert J. 1955-; Adams, William A. (Gildan, 2019)
Is your leadership a competitive advantage, or is it costing you? How do you know? Are you developing your leadership effectiveness at the pace of change?
Online resource; title from title details screen (OverDrive, viewed June 14, 2019)
Keywords: Leadership; BUSINESS & ECONOMICS; General; Downloadable audio books; Audiobooks; Livres audio